High Content Imaging of Barrett’s-Associated High-Grade Dysplasia Cells After siRNA Library Screening Reveals Acid-Responsive Regulators of Cellular TransitionsSummary - Sinead M. Phipps; Catherine E. Garry; Sepehr Kamal; James D. Johnson; John Gilmer; Aideen Long; Dermot Kelleher; Shane P. Duggan (Cellular and Molecular Gastroenterology and Hepatology, 2020)
Background & Aims: Esophageal adenocarcinoma (EAC) develops from within Barrett’s esophagus (BE) concomitant with gastroesophageal reflux disease (GERD). Wound healing processes and cellular transitions, such as epithelial–mesenchymal transitions, may contribute to the development of BE and the eventual migratory escape of metastatic cancer cells. Herein, we attempt to identify the genes underlying esophageal cellular transitions and their potential regulation by the low pH environments observed in GERD and commonly encountered by escaping cancer cells. Methods: Small interfering RNA library screening and high-content imaging analysis outlined changes in BE high-grade dysplasia (HGD) and EAC cell morphologies after gene silencing. Gene expression microarray data and low pH exposures studies modeling GERD-associated pulses (pH 4.0, 10 min) and tumor microenvironments (pH 6.0, constant) were used. Results: Statistical analysis of small interfering RNA screening data defined 207 genes (Z-score >2.0), in 12 distinct morphologic clusters, whose suppression significantly altered BE-HGD cell morphology. The most significant genes in this list included KIF11, RRM2, NUBP2, P66BETA, DUX1, UBE3A, ITGB8, GAS1, GPS1, and PRC1. Guided by gene expression microarray study data, both pulsatile and constant low pH exposures were observed to suppress the expression of GPS1 and RRM2 in a nonoverlapping temporal manner in both BE-HGD and EAC cells, with no changes observed in squamous esophageal cells. Functional studies uncovered that GPS1 and RRM2 contributed to amoeboid and mesenchymal cellular transitions, respectively, as characterized by differential rates of cell motility, pseudopodia formation, and altered expression of the mesenchymal markers vimentin and E-cadherin. Conclusions: Collectively, we have shown that low pH microenvironments associated with GERD, and tumor invasive edges, can modulate the expression of genes that triggered esophageal cellular transitions potentially critical to colonization and invasion.